Modelo de auditoría a los acuerdos de niveles de servicio – ANS que soportan los contratos de gestión de tecnología en las entidades bancarias colombianas (2022)
The purpose of this article is to learn about the ANS agreed between technological service providers and entities belonging to the banking sector in Colombia, in order to define and establish the risks associated with the management of services and technologies contracted with third parties. Process that will form the main basis for the design of a model for monitoring and controlling compliance with the contracts established between the various Colombian banking entities and their suppliers.